2008
DOI: 10.21236/ada488007
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Measures Related to Cross-Cultural Competence

Abstract: Public reporting burden for the collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden, to Washington Headquarters Services, Directorate for Information Operations and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…With both the current student population and workforce being so culturally diverse, it is critical that there is an understanding and appreciation of the cultural diversity. Although the conceptualization of cross-cultural competence is rather specific, ultimately, cross-cultural competencies are traits expected to lead individuals to perform certain behaviors; wherein these behaviors are then in turn expected to lead the desired outcomes that define the effectiveness of the purpose it was designed for (Ross & Thornson, 2008). Hence, the need of students to become flexible is a must among future graduates.…”
Section: International Journal Of Research Studies In Psychology 39mentioning
confidence: 99%
“…With both the current student population and workforce being so culturally diverse, it is critical that there is an understanding and appreciation of the cultural diversity. Although the conceptualization of cross-cultural competence is rather specific, ultimately, cross-cultural competencies are traits expected to lead individuals to perform certain behaviors; wherein these behaviors are then in turn expected to lead the desired outcomes that define the effectiveness of the purpose it was designed for (Ross & Thornson, 2008). Hence, the need of students to become flexible is a must among future graduates.…”
Section: International Journal Of Research Studies In Psychology 39mentioning
confidence: 99%
“…With both the current student population and workforce being so culturally diverse, it is critical that there is an understanding and appreciation of the culturally diverse. Although this conceptualization of cross-cultural competence is rather specific, ultimately, cross-cultural competencies are traits expected to lead individuals to perform in a certain behavior; wherein these behaviors are then in turn expected to lead the desired outcomes that define effectiveness of the purpose it was designed for (Ross & Thornson, 2008).…”
Section: International Journal Of Research Studies In Psychologymentioning
confidence: 99%
“…In response, while most cross-cultural studies are geared towards the cross-cultural adaptability or competence of the visiting individual, this case study details an empirical analysis of the cross-cultural flexibility of a host country's individuals. Within the various cross-cultural studies, the measures used and the construct they assess usually depends on the purpose and the type of competency required by a population of interest (Ross & Thornson, 2008). Hofstede ( 2001) suggested that the cross-cultural competence of an individual can be taught, but he indicated that personality factors also affect the levels of cross-cultural competencies that individuals can attain.…”
Section: Introductionmentioning
confidence: 99%
“…Kelebihan MASQUE yaitu memiliki korelasi yang rendah dengan social desirability yang diuji melalui pengkorelasian hasil pengukuran MASQUE dan Marlowe-Crowne Scores (Thornson & Ross, 2008). Munroe (2006) menjelaskan bahwa alat ukur yang dikembangkan oleh dirinya memiliki kelebihan karena melibatkan ketiga komponen dalam sikap untuk menyimpulkan sikap individu.…”
unclassified